Web-Based Solution for Efficient Waste Management - Pooja Sharma (International Journal of Intelligent Systems and Applications in Engineering, 2025)
Electronic waste (e-waste) is a rapidly growing worldwide environmental problem because of technological advances, reducing product lifespans, and big consumer demand [1],[2].E-waste contains vital substances such as gold, silver, and copper, as well as unsafe substances including lead, mercury, and cadmium, that could cause brilliant damage to human fitness and the surroundings if now not managed correctly[1]. Effective e-waste solutions consist of many techniques, which include recycling, reuse, sustainable product improvement, and public focus [3]. Methods to support the improvement of a round economic system and renewal, and to put into effect extended manufacturer responsibility (EPR) guidelines to hold groups accountable for the control of give up products. Further, new technology together with advanced analytical techniques and green extraction technologies can increase the recycling fee[2],[4]. Public schooling programs and worldwide cooperation are important to remedy the e-waste trouble and decrease its worldwide harm. The need for cooperation between authorities, enterprise, and consumers to create a smooth, in experienced future.